Multiobjective optimization of the trade-offs in smallholder dairy farming intensification - Mulinge, W.M.; Oluoch-Kosura,Willis; Staal, Steven J.; Mbogoh, S. (International Livestock Research Institute, 2004)
As farm sizes decline due to population pressure in the central highlands, smallholder farmers find it difficult to intensify dairying due to competition for resources by alternative crop and other enterprise. However, very little is known the nature of trade-offs the smallholder farmers experience in making decisions about the alternative choices of enterprises and synergy levels available for smallholder farmers. The purpose of this study was to develop and evaluate a framework for guiding choices on alternative agricultural enterprises and enterprise mixes in order to enable farmers to make more informed intensification strategies under varying market access and resource availability. The mathematical model of the decision problem is formulated in terms of multi-objective programming. It is shown that crops are not likely to replace dairy income, at least in the near term, as farm sizes decline if market access for dairy enterprise is assured. The findings indicate various strategies for smallholder farmers with small land holdings such as land-augmenting (off-farm feed resources, more intensive cropping and dairy enterprises, and continuous as well as mixed cropping). Smallholder farmers with larger land holding can engage in more labour intensive and profitable dairy production technologies. Secondly, profitable crop enterprises, especially in relatively large holdings, and relatively small amounts of labour allocated to fodder production seemed to be critical factors associated with low dairy productivity. A self-help insurance scheme is recommended to increase adoption of intensive dairy systems.